A two-stage hybrid gene selection algorithm combined with machine learning models to predict the rupture status in intracranial aneurysms - Li, Qingqing; Wang, Peipei; Yuan, Jinlong; Zhou, Yunfeng; Mei, Yaxin; Ye, Mingquan (Frontiers in Neuroscience, 2022)
An intracranial aneurysm is an abnormal swelling of cerebral vessels, and a subset of these intracranial aneurysms can rupture causing aneurysmal subarachnoid hemorrhage, often resulting in death or severe disability. Few studies have used an appropriate method of feature selection combined with machine learning by analyzing transcriptomic sequencing data to identify new molecular biomarkers. Following gene ontology and enrichment analysis, we found that the distinct status of intracranial aneurysms could lead to differential innate immune responses using all 913 differentially expressed genes, and considering that there are numerous irrelevant and redundant genes, we propose a mixed filter- and wrapper-based feature selection. First, we used the Fast Correlation-Based Filter (FCBF) algorithm to filter a large number of irrelevant and redundant genes in the raw dataset, and then used the wrapper feature selection method based on the he Multi-layer Perceptron (MLP) neural network and the Particle Swarm Optimization (PSO), accuracy and mean square error were then used as the evaluation criteria. Finally, we constructed a novel 10-gene signature (YIPF1, RAB32, WDR62, ANPEP, LRRCC1, AADAC, GZMK, WBP2NL, PBX1 and TOR1B) by the proposed two-stage hybrid algorithm FCBF-MLP-PSO and used different machine learning models to predict the rupture status in intracranial aneurysms. The highest accuracy value increased from 0.817 to 0.919 (12.5% increase), the highest area under ROC curve (AUC) value increased from 0.87 to 0.94 (8.0% increase), and all evaluation metrics improved by approximately 10% after being processed by our proposed gene selection algorithm. Therefore, these 10 informative genes used to predict rupture status of intracranial aneurysms can be used as complements to imaging examinations in the clinic, meanwhile, this selected gene signature also provides new targets and approaches for the treatment of ruptured intracranial aneurysms.